Antimicrobial activity of Leucas clarkei - Das, Surya Narayan; Patro, Varanasi Jagannath; Dinda, Subas Chandra (Bangladesh Journal of Pharmacology, 2012)
The antimicrobial potency of the whole plant of Leucas clarkei have been studied using the soxhlet extracts of petroleum ether, benzene, chloroform and ethanol extract against Gram-positive bacteria (two strains), Gram-negative bacteria (two strains) and two fungi strains by disc diffusion method. Micro-dilution methods, for the determination of minimal inhibition concentration (MIC) and the minimal bactericidal and fungicidal concentration (MBC, MFC). The ethanol extract at a concentration of 30 to 60 µg/disc and chloroform extract at a concentration 60 µg/disc showed significant activity against all the bacteria and fungus. All the extracts of L. clarkei have got moderate action but chloroform and ethanol extracts have got significant activity against Candida krusei, Candida albicans, Escherichia coli, Salmonella typhi, Staphylococcus aureus, and Bacillus subtilis. This may be due to phytochemicals such as phytosterols, alkaloid, tannins, phenolic compounds and flavonoids present in the extracts.